Plug’n’Play: Peeking out of the closet into the visibility paradigm - Tayranoğlu, Onur (Taideyliopiston Teatterikorkeakoulu, 2023)
This thesis examines the complexities of visibility within the LGBTQ+ struggle, challenging the dominant narrative that coming out is the sole path to liberation. Through a reflective exploration of the artistic work, Plug'n'Play, and the incorporation of embodied personal and communal strategies of LGBTQ+ individuals, the study delves into the potential of the closet as a counter framework that enables fluid and plural expressions of self. By interrogating the relationships between visibility, safety, and assimilation, the thesis critically questions the strategies that prioritize visibility within LGBTQ+ struggles. It argues that the rigid binary of outness and closetedness dissolves into ambiguous gray areas, especially through our interactions with the cyber technologies, where we need tools for negotiating the terms and agreements of visibility, enabling individuals to assert agency over how and to whom they become visible. Additionally, the thesis investigates queer sexual and gender visibility in the context of cyber technologies, aiming to identify artistic and conceptual tools derived from personal and communal strategies that empower individuals to negotiate visibility. The urgency and necessity of negotiation strategies are demonstrated in the first chapter, "Playing Safe." Drawing on insights from the book Trap Door (2017), edited by Reina Gossett, Eric A. Stanley and Johanna Burton, the study highlights the pitfalls of fixating on visibility and representation in visual culture, including social media, and underscores the lack of comprehensive institutional and governmental support structures. Moreover, the thesis challenges the dominant heteronormative frameworks that shape safety and risk perceptions, particularly by deconstructing the dynamics of surveillance and assimilation. It reveals how surveillance apparatuses rely on visibility to function, while also shaping the acceptability of LGBTQ+ representation and public visibility by imposing heteronormative behaviors over LGBTQ+ individuals. In conclusion, this thesis attempts to redefine the understanding of visibility as a condition, rather than an ultimate goal for the queer community. It emphasizes the fluidity and pluralism of performances within the closet and coming out, advocating for continual negotiation and the pursuit of agency within heteronormatively organized spaces. By critically analyzing the complexities of visibility and drawing on insights from the cyber realm, this study contributes to a nuanced understanding of LGBTQ+ visibility and suggests anonymity and encryption as tactics for navigating and negotiating visibility conditions. Ultimately, the thesis seeks to encourage LGBTQ+ individuals, artists, and researchers to seek tactics to challenge and reshape the sterilizing mainstream visibility discourse surrounding the community, not to fall into patriarchal, neoliberal, and white supremacist traps, by striving for a more inclusive and intersectional approach to queer struggles.
Keywords: LGBTQ+ politics; visibility; safety; risk; surveillance; digital technologies; cybersexuality; anonymity; encryption; artistic research; LAPS